2013
DOI: 10.2105/ajph.2013.301289
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Alcohol Prices and Outlet Densities in British Columbia, Canada: Estimated Impacts on Alcohol-Attributable Hospital Admissions

Abstract: Significant health benefits were observed when minimum alcohol prices in British Columbia were increased. By contrast, adverse health outcomes were associated with an expansion of private liquor stores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
127
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 26 publications
8
127
1
1
Order By: Relevance
“…In addition, although there is a limited research base for assessing the effectiveness of this strategy for reducing use and problems, Stockwell et al (2012) suggested that some reductions in sales and use followed from an increase in the minimum purchase price recently implemented in Alberta, Canada. Subsequent analyses of British Columbia data produced similar results (Stockwell et al, 2013).…”
Section: Alcohol Pricing and Taxesmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, although there is a limited research base for assessing the effectiveness of this strategy for reducing use and problems, Stockwell et al (2012) suggested that some reductions in sales and use followed from an increase in the minimum purchase price recently implemented in Alberta, Canada. Subsequent analyses of British Columbia data produced similar results (Stockwell et al, 2013).…”
Section: Alcohol Pricing and Taxesmentioning
confidence: 63%
“…More recently, another series of studies conducted in British Columbia provided insight into what happens in the wake of privatization. Specifi cally, the introduction of large numbers of stores resulting from partial privatization was associated with increases in alcohol consumption (Stockwell et al, 2009), alcohol-related mortality (Stockwell et al, 2011), and lower alcohol prices (Treno et al, 2013). On the other hand, there have been contrary fi ndings (Mulford et al, 1992;Trolldal, 2005aTrolldal, , 2005b.…”
Section: Privatization Effectsmentioning
confidence: 99%
“…Extensive modelling by the University of Sheffield 6 and studies from Canada 7,8 (where this policy has been introduced in several provinces) have both highlighted the benefits of setting a minimum unit price in reducing alcohol consumption, hospital admissions, and deaths caused by alcohol. This is currently the top alcohol policy recommendation from the UK public health community, 9 with the aim of increasing the price of the cheapest drinks that are often chosen by the heaviest drinkers and underage ones.…”
Section: What Work In Reducing Alcohol-related Harm and What Barriermentioning
confidence: 99%
“…12 Research indicates that reducing the density of these packaged liquor outlets may decrease harmful levels of alcohol consumption, especially in socially disadvantaged and/or lower socioeconomic status groups and young people. 13 There is a clear and strong relationship between the relative price of alcohol and alcohol consumption (including risky and hazardous consumption).…”
mentioning
confidence: 99%
“…5 Conversely, increased alcoholic beverage taxes and prices are related to reductions in alcohol use and related problems, 14 and significant health benefits have been observed when minimum alcohol prices are increased. 12 A recent survey in WA demonstrated that cheap liquor availability (typical of liquor superstores) influences increased alcohol purchase frequency, purchase quantity and consumption frequency and quantity. The purchase and consumption patterns of 18-29 year olds were most impacted by the availability of cheap alcohol.…”
mentioning
confidence: 99%